Efeitos dos tratamentos isolados e combinados de L-arginina e doxorrubicina sobre o estresse oxidativo em células de adenocarcinoma mamário humano (MCF-7) - Silva, Carlos Gabriel Coutinho da (2023)
It is known that Reactive Oxygen Species (ROS) are elevated in cancer cells and their effects in modulating cell growth depend on their concentration. For many years, doxorubicin (DOX) has been widely used to treat a wide spectrum of cancers as it is a highly potent chemotherapy drug. One of the actions of DOX is the increase in the generation of free radicals, oxidative damage to cellular DNA and mitochondria, which can promote apoptosis, autophagy, senescence, and necrosis. Clinically, treating breast cancer patients with DOX for a short period often causes cancer cells to develop resistance which leads to relapse and treatment failure. The action of amino acids such as L-arginine (L-ARG) is significant in anticancer therapy as it reduces the amount of ROS in metabolism. The objective was to investigate the effects of L-ARG on the MCF7 tumor line by evaluating possible changes in the expressions of proteins related to therapeutic resistance and oxidative stress after treatment alone and combined with dose-dependent DOX. The treatment groups were divided into: G1 (L-ARG), G2 (DOX) and G3 (L-ARG+DOX). Our study demonstrated reduced cell viability and oxidative stress increased with isolated treatments in a dose-dependent manner. Furthermore, treatment with L-ARG reduced the expression of catalase (CAT) and nuclear factor erythroid 2 (NFR2) and increased the expression of NOX2 at higher concentrations (3200ug/mL + 4uM); DOX treatment reduced CAT in higher concentrations; L-ARG + DOX reduced CAT at lower doses, increased NOX2 and reduced NFR2 at all concentrations. Similar analyzes were found when doxorubicin was combined with other drugs. In conclusion, the combined treatment of L-ARG with DOX may be an indication to overcome therapeutic resistance and be a possible therapy in the treatment of breast cancer.